The Dual Role of Environmental Literacy and Spatial Intelligence in Developing Students' Ecological Problem-Solving Competencies - Fellix Rimba; Annisa Joviani Astari; Nandi; Dismo Katiandagho (The Indonesian Institute of Science and Technology Research, 2026)
Environmental problems such as waste, pollution, climate change, and the depletion of natural resources have exposed the Earth to the threat of extreme global warming. However, students often face difficulties in addressing these issues due to limited involvement in environmental activities and underdeveloped cognitive skills. This study aims to analyze how environmental literacy and spatial intelligence among high school students influence their ability to solve environmental problems. To achieve this, we conducted a questionnaire survey involving 248 students from 11th-grade social science classes. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) techniques. The findings indicate that: (1) environmental literacy has a significant influence on students’ environmental problem-solving ability, with a path coefficient of 0.317 (categorized as good); (2) spatial intelligence also influences problem-solving ability, with a coefficient of 0.422 (good); and (3) the combined structural model of environmental literacy and spatial intelligence shows a stronger influence on problem-solving ability, with a coefficient of 0.590 (categorized as high). Given these findings, it is essential to enhance students' understanding of ecological challenges by improving both their environmental literacy and spatial intelligence. This can be achieved through effective geography learning strategies and by encouraging active student participation in environmental activities. Such a holistic approach is crucial to equip students with the knowledge and skills necessary to address and resolve pressing environmental issues effectively.